Synthesis of Nω‐Phospho‐l‐arginine by Biocatalytic Phosphorylation of l‐Arginine. Issue 1 (2nd December 2016) - Schoenenberger, Bernhard; Wszolek, Agata; Milesi, Thomas; Brundiek, Henrike; Obkircher, Markus; Wohlgemuth, Roland
Abstract: The N ω ‐phospho‐l ‐arginine energy‐buffering system is mainly present in invertebrates for regulating energy requirements when it is highly needed, such as in the flight muscles of an insect or when energy supply fluctuates, as in the medically important protozoa Trypanosoma brucei, Trypanosoma cruzi, and Leishmania major . The lack of availability of this important metabolite was due to a tedious chemical procedure, by which N ω ‐phospho‐l ‐arginine was prepared in over 5 reaction steps in a low yield. Therefore, we aimed at improving the synthetic methodology for the preparation of this important metabolite. As site‐ and enantioselective kinases have been very useful catalysts for biocatalytic phosphorylations in straightforward syntheses of phosphorylated metabolites, a stable and selective arginine kinase has been selected for the selective phosphorylation ofl ‐arginine. The Arg gene has been cloned and expressed in E. coli and a highly active arginine kinase has been prepared. A simple synthesis of N ω ‐phospho‐l ‐arginine has been developed by arginine kinase catalyzed phosphorylation ofl ‐arginine combined with the recycling of the phosphorylating agent ATP by using the phosphoenolpyruvate/pyruvate kinase system. After standard work‐up, the desired product N ω ‐phospho‐l ‐arginine was obtained in gram quantities and in one step. Abstract : Biocatalytic phosphorylation : A straightforward one‐step synthesis of N ω ‐phospho‐l ‐arginine has been developed by arginine kinase catalyzed phosphorylation ofl ‐arginine by using the phosphorylating agent ATP, which was recycled with the phosphoenolpyruvate/pyruvate kinase regeneration system for the selective phosphorylation ofl ‐arginine. A highly active and stable arginine kinase has been prepared by cloning and expressing the argK gene in E. coli .